PEMILIHAN KARYAWAN TERBAIK PADA BANK DKI DENGAN METODE TOPSIS - Syaifur Rahmatullah; Robi Aziz Zuama; Aditia Darmawan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The selection of the best employees is very important to be done by the company in order to see the quality of human resources and to increase the productivity and achievement of a company. The problem with Bank DKI is that there is no assessment for the best employees, causing employees to have low work motivation. In the process of selecting the best employee candidates, the company has not used alternative methods to produce the best candidates efficiently and accurately. In supporting these needs, a decision system is needed that can produce a system to facilitate the determination and selection of the best employees through several relevant criteria.